How students’ perceptions of teachers’ autonomy-supportive behaviours affect physical activity behaviour: an application of the trans-contextual model - Pihu, M.; Hein, V.; Koka, A.; Hagger, Martin (Taylor and Francis Group, 2008)
The aim of this study was to assess a modified version of the trans-contextual model (Hagger, Chatzisarantis, Culverhouse, & Biddle, 2003) based on self-determination theory (Deci & Ryan, 1985) and the theory of planned behaviour (Ajzen, 1985). The modified version included two additional components: use of learning strategies and positive general feedback. It was hypothesized that students’ perceptions of how they use learning strategies taught by their physical education (PE) teachers and perceived positive general feedback would influence students’ intrinsic motivation, intentions, and physical activity behaviour in a leisure-time context through intrinsic motivation in PE. A structural equation model supported the hypotheses and demonstrated that the use of learning strategies and perceived positive general feedback in PE indirectly influenced intrinsic motivation in leisure time through the effect of intrinsic motivation in PE. There was a direct effect of perceived positive general feedback on physical activity behaviour as well as an indirect effect through the motivational sequence.